(untitled) (Bangladesh Medical Journal Khulna, 2014)
The study was done to evaluate the safety and clinical outcome of routine caesarean myomectomy. This was a prospective descriptive study done in Obstetrics & Gynaecology department of Khulna Medical College Hospital & Sadar Hospital, Satkhira and two private clinics in Khulna city. Over a period of 4 years from July, 2009 to June, 2013, twenty one cases of caesarean myomectomy were presented. Our technique comprised of infiltration of vasoconstritive agent (ceprecin) before nucleation of myoma, myoma cavity accomplished by using "U" stitches of myometrial closure, routine use of oxytocin in post operative period for 24 hours. It was seen in this study that the mean age of the patients was 31.7 years and most of the cases (71.43%) were primigravida. Caesarean myomectomy done in term pregnancy was 85.71%. Elective surgery was done in 85.71% and emergency surgery was 14.29%. Two leading indications for caesarean section were malpresentation/ abnormal lie in 42.85% and uterine fibroid in 23.81%. Fibroid in lower uterine segment for selective myomectomy was 61.90%. Maximum (21,65.63%) fibroids were removed from the lower uterine segment and 22 (68.75%) of the fibroids were between 5 cms to 10 cms in size. The morbidities encountered were anaemia with blood transfusion in 2 (9.52%) and post partum pyrexia in 1 (4.76%) patients. No woman needed hysterectomy. Caesarean myomectomy may be done routinely by experienced surgeon and routine use of vasopressin into myoma capsule to combat uterine atony & severe bleeding. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18232 Bang Med J (Khulna) 2013; 46 : 7-11